Optimalisasi Penerapan Prinsip Transparansi Dalam Pengelolaan Perum Perhutani - Pebriaty, Ade Evi; Arwanto, Bambang (Indonesian Journal Publisher, 2024)
Juridically, the implementation of transparency principles as part of Good Corporate Governance in Perum Perhutani has been initiated, though not yet fully optimized. Perum Perhutani has provided easy access to information and strives to maintain good relationships with stakeholders through various activities and media, in compliance with OJK Regulation No. 31/POJK.04/2015 on Disclosure of Material Information by Issuers or Public Companies. Transparency in material information builds public trust in a company's performance, necessitating specific regulations governing Annual Reports, as outlined in Chairman of the Capital Market Supervisory Board and Financial Institution Decision No. KEP-431/BL/2012 regarding Submission of Annual Reports by Issuers or Public Companies. Public access to information enables understanding and monitoring of management activities, fostering professional and ethical implementation of corporate vision and mission, considering all stakeholders. Ultimately, optimal application of Good Corporate Governance serves as a collective commitment to professional and ethical company conduct, minimizing conflicts of interest and legal issues, thereby enhancing product quality, company management, corporate value development, and reputation improvement in the long run.